Making Sustainable Commitments : An Environment Strategy for the World Bank - World Bank (Washington, DC, 2013)
The report outlines the work of the World Bank in addressing client countries with environmental challenges, and, aims to ensure the lending program integrates principles of environmental sustainability. It highlights that the challenge of development assistance lies in working with clients to implement policies, programs, and investments that distribute the gains of development in an equitable manner, by reducing poverty, and avoiding sacrificing the interests of future generations, to meet the needs of the current one, and in addition, it builds on the consensus that natural resources, and environmental assets must be managed sustainably. This environment strategy links environment and development with the qualities of life, growth, and regional and global commons, by enhancing the livelihoods of poor people who are heavily dependent on the productivity of ecosystems, and natural resources; by preventing, and reducing environmental health risks; by supporting policy, regulatory, and institutional frameworks for sustainable environmental management, and, by supporting private sector development, to help improve, and protect the regional, and global environment, i.e., climate change, land degradation, forests, water resources, and biodiversity. The strategy stresses on strengthening analytical, and advisory activities, on country-level environmental analysis, and on strategic sectoral, regional, and policy-focused environmental assessments, through improved project design, performance criteria, and capacity development, while emphasizing on the commitment of countries towards sustainable development.